Calendrical variations in Second Temple Judaism : new perspectives on the "Date of the Last Supper" debate - Saulnier, Stéphane. (Supplements to the Journal for the Study of Judaism, 2012)
Starting from the seminal work of the French scholar Annie Jaubert on the date of the Last Supper, the present work revisits known - and identifies new - calendrical issues in the literature of Second Temple Judaism. The research supports the conclusion that all known calendrical traditions functioned on the tenet that orthopraxis in ancient Judaism meant close interconnection between cultic and agricultural cycles. From this perspective the book removes the calendrical objection leveled at the Jaubertian theory. Further, the research brings new light on current debates about Qumran calendrical documents and proposes the identification of a previously unknown calendrical polemic in the Astronomical Book of Enoch concerning the synchronization of the 364DY tradition with the lunar cycle.